2015
DOI: 10.1097/mpa.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Leucine-Rich α2-Glycoprotein-1 in Sera of Patients With Pancreatic Cancer

Abstract: These results suggest that serum LRG-1 is a promising biomarker for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 21 publications
2
54
0
Order By: Relevance
“…10 An increase in serum LRG was also observed in other diseases such as rheumatoid arthritis, infection, heart failure, 12 and malignant diseases. 13 Moreover, our recent study clearly demonstrated an association between LRG upregulation and clinical activity of IBD, which was superior to conventional serological biomarkers. 10 However, comprehensive analysis of the correlation between serum LRG and endoscopic disease activity of UC has not been performed.…”
Section: Introductionmentioning
confidence: 77%
“…10 An increase in serum LRG was also observed in other diseases such as rheumatoid arthritis, infection, heart failure, 12 and malignant diseases. 13 Moreover, our recent study clearly demonstrated an association between LRG upregulation and clinical activity of IBD, which was superior to conventional serological biomarkers. 10 However, comprehensive analysis of the correlation between serum LRG and endoscopic disease activity of UC has not been performed.…”
Section: Introductionmentioning
confidence: 77%
“…A role for LRG1 has been suggested in promoting angiogenesis through activation of the TGF-b pathway (40). Apart from PDAC, increased LRG1 plasma levels have also been found in other cancer types (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit anti‐LRG1 antibody (1:500; HPA001888; Atlas Antibodies, Stockholm, Sweden) was used for IHC. As LRG1 expression in tumor cells was primarily localized in the cytoplasm and the pattern of staining was homogeneous and diffuse, LRG1 expression was evaluated by the intensity of stained cancer samples as previously reported . Liver tissues were used as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, recent studies have reported that LRG1 can be used as a biomarker in several types of cancer such as ovarian, lung, biliary tract, and hepatocellular carcinoma . Serum LRG1 is also detected in patients with malignancies and associated with progression of malignancies . However, no reports exist on the clinical significance of LRG1 expression in gastric cancer.…”
mentioning
confidence: 99%